Anna's Fight for Hope 1931 - Grote, Joann A.; Nang ChanYeema (Uhrichsville, Ohio USA Barbour Publishing, Inc., 2004)
Anna and Fred do what they can to bring love and help to families during the Great Depression of 1931.
Keywords: Story Collection